The role of artistic elements in embodying value variables in television drama - Fatima Essam Hamdoun; Athraa mohammed hassan (الاكاديمي)
The research aims to reveal the importance of artistic elements in addressing the value changes that occurred in society, which in turn are affected by the continuous development of life, and that this change has an impact on the behavior of the individual and society, and by virtue of openness to the world that allowed the exchange of cultures and identification of the most important values for societies, through The media and social media, including television, which works to convey the life of societies and their reality, and the largest share of the television drama was and still simulates social action, and is embodied in the form of a television series affected by social problems, so it presents them trying to find solutions and identify the effects and causes of those problems, or to change Concepts of the recipient and influence on his ideas and beliefs